Impact of model fidelity in factory layout assessment using immersive discrete event simulation - Petti, Alessandro; Hutabarat, Windo; Oyekan, John; Turner, Christopher J.; Tiwari, Ashutosh; Prajapat, Neha; Gan, Xiao-Peng (Operational Research Society, 2016)
Discrete Event Simulation (DES) can help speed up the layout design process. It offers further benefits when combined with Virtual Reality (VR). The latest technology, Immersive Virtual Reality (IVR), immerses users in virtual prototypes of their manufacturing plants to-be, potentially helping decision-making. This work seeks to evaluate the impact of visual fidelity, which refers to the degree to which objects in VR conforms to the real world, using an IVR visualisation of the DES model of an actual shop floor. User studies are performed using scenarios populated with low- and high-fidelity models. Study participant carried out four tasks representative of layout decision-making. Limitations of existing IVR technology was found to cause motion sickness. The results indicate with the particular group of naïve modellers used that there is no significant difference in benefits between low and high fidelity, suggesting that low fidelity VR models may be more cost-effective for this group.
Keywords: Layout design; Virtual reality; Oculus rift; Factory layout; Virtual environment; Discrete event simulation; Model fidelity